Telomerase reverse transcriptase and neurodegenerative diseases - Yu, Xin; Liu, Meng-Meng; Zheng, Cai-Yun; Liu, Yu-Tong; Wang, Zhuo; Wang, Zhan-You (Frontiers in Immunology, 2023)
Neurodegenerative diseases (NDs) are chronic conditions that result in progressive damage to the nervous system, including Alzheimer’s disease (AD), Parkinson’s disease (PD), Huntington’s disease (HD), and Amyotrophic lateral sclerosis (ALS). Age is a major risk factor for NDs. Telomere shortening is a biological marker of cellular aging, and telomerase reverse transcriptase (TERT) has been shown to slow down this process by maintaining telomere length. The blood-brain barrier (BBB) makes the brain a unique immune organ, and while the number of T cells present in the central nervous system is limited, they play an important role in NDs. Research suggests that NDs can be influenced by modulating peripheral T cell immune responses, and that TERT may play a significant role in T cell senescence and NDs. This review focuses on the current state of research on TERT in NDs and explores the potential connections between TERT, T cells, and NDs. Further studies on aging and telomeres may provide valuable insights for developing therapeutic strategies for age-related diseases.